In vivo Dominant-Negative Effect of an SCN5A Brugada Syndrome Variant - Doisne, Nicolas; Grauso, Marta; Mougenot, Nathalie; Clergue, Michel; Souil, Charlotte; Coulombe, Alain; Guicheney, Pascale; Neyroud, Nathalie (Frontiers in Physiology, 2021)
Loss-of-function mutations in the cardiac Na+ channel alpha-subunit Nav1.5, encoded by SCN5A, cause Brugada syndrome (BrS), a hereditary disease characterized by sudden cardiac death due to ventricular fibrillation. We previously evidenced in vitro the dominant-negative effect of the BrS Nav1.5-R104W variant, inducing retention of wild-type (WT) channels and leading to a drastic reduction of the resulting Na+ current (INa). To explore this dominant-negative effect in vivo, we created a murine model using adeno-associated viruses (AAV). Methods: Due to the large size of SCN5A, a dual AAV vector strategy was used combining viral DNA recombination and trans-splicing. Mice were injected with two AAV serotypes capsid 9: one packaging the cardiac specific troponin-T promoter, the 5’ half of hSCN5A cDNA, a splicing donor site and a recombinogenic sequence; and another packaging the complementary recombinogenic sequence, a splicing acceptor site, the 3’ half of hSCN5A cDNA fused to the gfp gene sequence, and the SV40 polyA signal. Eight weeks after AAV systemic injection in wild-type (WT) mice, echocardiography and ECG were recorded and mice were sacrificed. The full-length hSCN5A-gfp expression was assessed by western blot and immunohistochemistry in transduced heart tissues and the Na+ current was recorded by the patch-clamp technique in isolated adult GFP-expressing heart cells. Results: Almost 75% of the cardiomyocytes were transduced in hearts of mice injected with hNav1.5 and ~30% in hNav1.5-R104W overexpressing tissues. In ventricular mice cardiomyocytes expressing R104W mutant channels, the endogenous INa was significantly decreased. Moreover, overexpression of R104W channels in normal hearts led to a decrease of total Nav1.5 expression. The R104W mutant also induced a slight dilatation of mice left ventricles and a prolongation of RR interval and P-wave duration in transduced mice. Altogether, our results demonstrated an in vivo dominant-negative effect of defective R104W channels on endogenous ones. Conclusion: Using a trans-splicing and viral DNA recombination strategy to overexpress the Na+ channel in mouse hearts allowed us to demonstrate in vivo the dominant-negative effect of a BrS variant identified in the N-terminus of Nav1.5.